2014
DOI: 10.2478/meceng-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Stack Parameters Effect on the Performance of Anharmonic Resonator Thermoacoustic Heat Engine

Abstract: A thermoacoustic heat engine (TAHE) converts heat into acoustic power with no moving parts. It exhibits several advantages over traditional engines, such as simple design, stable functionality, and environment-friendly working gas. In order to further improve the performance of TAHE, stack parameters need to be optimized. Stack’s position, length and plate spacing are the three main parameters that have been investigated in this study. Stack’s position dictates both the efficiency and the maximum produced acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The thermal penetration depth is the distance surrounding the stack plate where thermoacoustic effects are present [4]. This finding was also supported by Nouh et al [15] where their numerical study concluded that the optimal stack spacing was 2.4δk.…”
Section: Introductionmentioning
confidence: 52%
“…The thermal penetration depth is the distance surrounding the stack plate where thermoacoustic effects are present [4]. This finding was also supported by Nouh et al [15] where their numerical study concluded that the optimal stack spacing was 2.4δk.…”
Section: Introductionmentioning
confidence: 52%
“…For the standing-wave engine or refrigerator, Babaei and Siddiqui 50 apply parametric variation in their own thermoacoustic model to predict the optimum length of the engine and the position of the stack within it, from the point of view of the thermal efficiency or the coefficient of performance, respectively. In a similar analysis for standing-wave prime movers, Nouh et al 144 use calculations with DeltaE to determine the optimum stack position for a variable area resonator, the results being relatively insensitive to the stack length. With helium at 10 bar, the plate spacing for maximum efficiency was 2.4 times the thermal penetration depth in this case.…”
Section: Passive Control Of Engines Through Designmentioning
confidence: 99%
“…600W of heat source could produce 27W of acoustic power, as reported by Feldman on his PhD dissertation [4]. Investigations on the theory that could explain the phenomena, have been done by later researchers, to find a possible optimization and operations of the actual system [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%